Selected Political Hoax Cases on Social Media: Multimodal in Forensic Linguistics - Tri Astuti, Wulan; Mulyadi, Ari (Policy & Governance Review, 2025)
This study explores the complexities of political hoaxes on social media through the lens of multimodal forensic linguistics, focusing on integrating verbal and visual elements in the construction and dissemination of misinformation. By analyzing five prominent political hoaxes in the Indonesian context, the research applies a multimodal pragmatic framework, incorporating semantic representations of an individual mode, semantic representation of multimodal mode, and inferential meanings elaborated using post-truth escapism to examine the mechanisms of hoax narrative construction. The findings reveal how hoaxes use multimodal meanings across modes to manipulate public opinion and foster post-truth realities. The study highlights the critical role of multimodal elements, such as visual mode combined with emotive language in verbal mode, to reinforce hoaxes and shape ideologically biased narratives. It further discusses the implications of these findings for forensic linguistic analysis, emphasizing the need for refined methodologies that incorporate both verbal and visual modes in legal discourse. The study contributes to the growing field of multimodal forensic linguistics by offering a comprehensive approach to analyzing political hoaxes and their strategy for eroding trust in factual information.